Intravenous lipid emulsion therapy in three cases of canine naproxen overdose. (13th May 2015) - Herring, Jennifer M.; McMichael, Maureen A.; Corsi, Raffaella; Wurlod, Virginie
Abstract Objective To report a case series of canine naproxen overdoses successfully treated with intravenous lipid emulsion therapy (IVLE). Series Summary Three dogs were presented for acute ingestion of naproxen and were treated with IVLE. Baseline and post treatment serum naproxen concentrations were measured. The first exposure involved ingestion of 61 mg/kg of an over‐the‐counter naproxen formulation in a 7‐month‐old male intact Labrador Retriever. Pre‐IVLE toxin concentration assessed by high performance liquid chromatography (HPLC) was 73 μg/mL with a one‐hour post‐IVLE concentration decreasing to 30 μg/mL. The second and third exposures were 3‐year‐old female spayed Pembroke Welsh Corgi dogs from the same family, presented for potential ingestion of up to 207 mg/kg of a prescription strength naproxen formulation. Pre‐IVLE naproxen concentration by HPLC for case 2 was 30 μg/mL with a reduction to 12 μg/mL and 7.2 μg/mL 1 and 3 hours post‐IVLE treatment, respectively. For case 3, pre‐IVLE naproxen concentration by HPLC was 86 μg/mL with post concentrations at 21 μg/mL one hour and 10 μg/mL 3 hours post‐IVLE administration. New or Unique Information Provided Naproxen is a nonsteroidal anti‐inflammatory drug with a long half‐life and narrow margin of safety in dogs. Ingestion of > 5 mg/kg has been associated with adverse gastrointestinal effects, including ulceration. At doses > 10–25 mg/kg, acute kidney failure has been reported, and at doses > 50 mg/kg, neurologic abnormalities occur. This is the first reported use of IVLE for treatment of naproxen overdose with documented decrease in serum toxin concentrations shortly after administration. No long‐standing gastrointestinal, renal, or neurologic effects occurred in these dogs.